Impact of reactive oxygen species on antioxidant capacity of male reproductive system. (September 2016) - Riaz, Muhammad; Mahmood, Zahed; Shahid, Muhammad; Saeed, M Usman Qamar; Tahir, Imtiaz Mahmood; Shah, SM Ali; Munir, Naveed; El-Ghorab, Ahmed
The present research work was aimed to study the mutual interaction of reactive oxygen species (ROS) and basal cells antioxidant capacity in the male reproductive system and to further establish the association between selected heavy metals and stress markers. Total oxidant status (TOS) and total antioxidant status (TAS) of serum and seminal plasma were determined by automated photometric methods. The concentrations of Selenium (Se), Lead (Pb), and Cadmium (Cd) were determined by using atomic absorption spectrophotometer. The TOS was increased significantly ( P <0.05) in seminal plasma as well as in the serum of the infertile group when compared with the fertile group. On the other hand, the TAS of the infertile group was found to be noticeably decreased ( P <0.05) when compared with the TAS of the fertile group. Among the heavy metals, a noticeably lower concentration of Se was detected in the infertile group whereas markedly elevated levels of Cd and Pb were observed in the infertile group compared with the fertile group. Among the infertile group a significant inverse correlation (r = −0.521, P <0.05) was observed between Se and TOS and between Cd and Pb (r = −0.407, P <0.05). Contrarily among the infertile group a considerable positive relationship was established between Se and TAS (r = 0.507, P <0.05). It was concluded that the oxidant stress reduces the antioxidant activity in infertile men by elevating the production of ROS. A lower concentration of Se and elevated levels of Pb and Cd explain the individual's exposure to these heavy metals. The study also revealed that the heavy metal toxicity contributes significantly to male infertility.